The Role of Job Satisfaction and Work Commitment in Moderating Transformational Leadership on Nurses' Performance Mediated By Organizational Citizenship Behavior (Study Of Nurses In South Konawe District) - Sjarif, Susman; Syaifuddin, Dedy Takdir; Nasrul, Nasrul; Yusuf, Yusuf (Journal of Neonatal Surgery, 2025)
This study aims to analyze the influence of transformational leadership on performance and Organizational Citizenship Behavior (OCB) among nurses in South Konawe Regency. Additionally, this study explores the role of OCB in mediating the relationship between transformational leadership and nurses' performance. The study also examines how job satisfaction and work commitment may strengthen or weaken the relationship between transformational leadership and both performance and OCB of nurses. On the other hand, the role of job satisfaction and work commitment is also analyzed in relation to OCB and nurses' performance. The research respondents consisted of 200 nurses, and data were collected through questionnaires and SEM modeling. The results show that transformational leadership has a positive and significant impact on nurses' performance and encourages organizational citizenship behavior (OCB) among nurses. OCB is found to have a positive influence on nurses' performance, creating a more productive work environment. Furthermore, transformational leadership significantly affects nurses' performance through the mediation of OCB. However, job satisfaction does not moderate the relationship between transformational leadership and nurses' performance, nor does it moderate the effect of OCB on nurses' performance. External factors such as high workload and limited facilities may weaken the influence of leadership on OCB and performance. Conversely, work commitment acts as a moderator that strengthens the relationship between transformational leadership and performance, as well as OCB and nurses' performance, although a negative influence of work commitment on OCB and performance is found. These findings indicate that while OCB enhances performance, high work commitment may limit nurses' motivation to engage in extra-role behavior, ultimately reducing their performance.